PENGARUH KEMAMPUAN BERADAPTASI TERHADAP PSYCHOLOGICAL WELL-BEING DENGAN DUKUNGAN SOSIAL SEBAGAI VARIABEL MEDIATOR PADA SISWA MUHAMMADIYAH BOARDING SCHOOL BUMIAYU - Amanda Umeilika; Dyah Astorini Wulandari; Retno Dwiyanti; Fatin Rohmah Nur Wahidah (CV. Denasya Smart Publisher, 2026)
Life in a boarding school requires students to adjust to a new environment, strict rules, and living far away from their parents, which can affect their psychological well-being. Students at Muhammadiyah Boarding School Bumiayu experience difficulties in adapting and receive limited social support, which in turn influences their psychological well-being. This study aims to examine the effects of adaptability on psychological well-being, with social support as a mediating variable. This research employed a quantitative method with a sample of 169 students from Muhammadiyah Boarding School Bumiayu, selected using simple random sampling. Data analysis was conducted using simple linear regression and mediation analysis. The results show that adaptability has a significant effect on psychological well-being, with an F value of 119.970 and a significance level of < 0.001. Adaptability accounts for 41.8% of the variance in psychological well-being. Furthermore, adaptability has a significant effect on social support, with an F value of 25.425 and a significance level of < 0.001, explaining 13.2% of the variance in social support. Social support also has a significant effect on psychological well-being, with an F value of 35.728 and a significance level of < 0.001, contributing 17.6% to psychological well-being. In addition, social support is proven to mediate the effect of adaptability on psychological well-being, as indicated by the indirect effect confidence interval that does not include zero (BootLLCI = 0.0748; BootULCI = 0.3883). It can be concluded that adaptability has a significant effect on psychological well-being both directly and indirectly through social support.